Avaliação de desempenho de sistema de vedação vertical de bloco de solo-cimento conforme NBR 15575 referente à habitabilidade e sustentabilidade - Giorgi, Priscila (2016)
The Industrial Revolution generated two parallel phenomena during the twentieth century: increased distribution of wealth and reduced energy costs, causing a large increase in energy consumption. With the international oil crisis in the 1970s, materials used until that time such as concrete, steel and glass, began to be seen as energy-intensive materials. Society began to seek buildings with minimal environmental impact, using materials that generate a smaller amount of energy, waste and pollution and CO2 emissions in the atmosphere and provide greater potential for reincorporation into nature. In this scenario, raw soil as a building material has become an alternative for the development of sustainable buildings, but also to improve the livability of housing for the low-income population in the country. Among various construction materials, raw soil-cement, which is cured without burning, is raw soil pressed and stabilized with Portland cement, which is already regulated by the Brazilian Technical Standards Association (ABNT) and possesses many advantages related to its manufacturing and use. To increase its acceptance and verify its efficiency as a building material for social housing, it is necessary to investigate its properties and performance. Thus, the present study aimed to evaluate the performance of an external vertical sealing system composed of soil-cement blocks without structural function for social housing, following determinations of NBR 15575 (2013), focusing on the requirements of Habitability and Sustainability. The habitability require the heat action and thermal shock test. Firstly, using the particle size analysis and liquid limit and plastic limit test, to characterize the compostion of the ground on which the block was used. The bodies-of-proof were tested in The laboratory of Structural Models and Tests (Laboratório de Ensaios e Modelos Estruturais LEME), at the Federal University of Rio Grande do Sul (UFRGS), Porto Alegre, RS, and consisted of two full scale walls. The system met limits set by standards for tightness against rainwater and heat action and thermal shock, but not for permeability to water. The vertical sealing system composed of hollow blocks of soil-cement has great potential for application in the construction of social housing, but there is still a need for more studies on the system.